Legal culture of the person in a state of law - Бородін, Іван (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The basis of the legal culture of society and each citizen the constitutional relationship between the individual and the public authorities. This implies a clear and steady implementation of the Constitution of Ukraine, the reality is enshrined in the rights and freedoms: the right to elect and be elected to government, freedom of speech, assembly and so on. The activities of state bodies and officials must be made by common law principle "allowed only what is directly provided by law."